Refleksi Guru Bahasa Indonesia Dalam Pembelajaran Berbasis Kurikulum Merdeka Di SMP Negeri 2 Padamara - Adina Anisnaeni Rizqina; Ngifat Khoerunnisa; Chafit Ulya (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2023)
Education plays a very important role in developing the human resource potential of a country. This research examines how Indonesian language teachers at SMP Negeri 2 Padamara reflect on their experiences in facing the newly implemented Merdeka Curriculum. The Independent Curriculum is an educational approach that focuses on student needs, so teachers face additional challenges and responsibilities in implementing it. This research aims to explore the perspectives and experiences of Indonesian language teachers at SMP Negeri 2 Padamara in facing the Independent Curriculum. The research method used was descriptive qualitative with interview techniques with Indonesian language teachers at SMP Negeri 2 Padamara. Data validity testing was carried out using data source triangulation techniques. The research results show that the Merdeka Curriculum is considered relevant and oriented towards meeting student needs. Teachers have tried a variety of tailored learning strategies, including content, process, and product differentiation. Apart from that, this research also highlights the important role of learning modules and media in the Independent Curriculum, as well as the importance of In House Training (IHT) as an effort to increase teachers' understanding of the newly implemented curriculum. It is hoped that these findings can provide a valuable contribution in the development of educational strategies and provide the necessary support to teachers and other educational institutions that are implementing the Merdeka Curriculum.